Slipstream : a novel - Maril, Madge (Simon & Schuster Paperbacks, 2025)
"In the high-speed world of Formula 1, documentarian Lilah teams up with racing driver Arthur Bianco for a whirlwind of revenge--and perhaps something more. Lilah Graywood never imagined she'd be spending her summer amidst the roaring engines and adrenaline-fueled world of Formula 1 racing. As a serious documentarian, her passion lies in capturing the raw, unfiltered truth. But when her best friend, business co-owner, and secret boyfriend Max decides to pivot their documentary company to film the Ignition Energy Drink Racing team, Lilah is thrust into a world she despises. Her disdain turns to fury when Max blindsides her, not only ending their relationship but also threatening the company she painstakingly built. Enter Arthur Bianco, the charismatic and enigmatic F1 reserve driver whose career is as tumultuous as the races he dreams of winning. Initially, Lilah is supposed to document Arthur's relegation to backup driver, but together they concoct a plan to take control of Max's documentary, each with their own motives--Lilah's revenge and Arthur's redemption. Their secret alliance promises to change the narrative, both on and off the track. As they navigate the glamorous circuits and behind-the-scenes secrets of Formula 1, an unexpected speedbump forces Lilah and Arthur's partnership to evolve into a fake relationship that feels all too real. The chemistry between them is off-limits and undeniable, and as Arthur's cinematic comeback plays out over the hot globe-trotting summer, Lilah finds herself drawn to his true charm and hidden vulnerability. But as the cameras roll and the world watches, Lilah must confront her own feelings and the reality that no script can dictate the course of true love."-- Amazon.com.